BRAF inhibition for advanced locoregional BRAF V600E mutant melanoma: a potential neoadjuvant strategy. Issue 1 (February 2016) - Sloot, Sarah; Zager, Jonathan S.; Kudchadkar, Ragini R.; Messina, Jane L.; Benedict, Jacob J.; Gonzalez, Ricardo J.; DeConti, Ronald; Turner, Leslie M.; McCardle, Timothy; Smalley, Keiran S.M.; Weber, Jeffrey S.; Sondak, Vernon K.; et al.
Abstract : Selective BRAF inhibitors (BRAFi) yield objective responses in 50% of patients with metastatic BRAF V600E mutant melanoma. Adding an MEK inhibitor increases this response rate to 70%. Limited data are available on the outcomes of unresectable stage III patients, and it remains unclear whether BRAF-targeted therapy can be utilized as a neoadjuvant strategy. Data on patients with advanced locoregional BRAF V600E mutant melanoma treated with BRAF-targeted therapy at Moffitt Cancer Center were analyzed to determine response rates, subsequent resection rates after tumor downsizing, pathologic responses, and patient survival. Fifteen patients with locoregional disease treated with BRAF-targeted therapy, either BRAFi alone (vemurafenib; 11 patients) or a combination of BRAFi and an MEK inhibitor (dabrafenib plus trametinib or placebo; four patients), were identified. The median age was 50 years; the median follow-up was 25.4 months. The median BRAF-targeted therapy treatment duration was 6.0 months (range 1.2–29.4 months). Response Evaluation Criteria In Solid Tumors-based evaluation demonstrated objective response in 11 patients (73.3%). Six patients underwent resection of the remaining disease after therapy. Pathological analysis showed complete pathologic response ( n =2), partial pathologic response ( n =2), or no pathologic response ( n =2). Four of six patients undergoing surgery have been alive for more than 2 years, including three patients currently free from active disease. No complications attributable to BRAF-targeted therapy were observed in the perioperative period. Dose reduction or discontinuation because of toxicities occurred in 10/15 patients. Neoadjuvant BRAF-targeted therapy may be effective in advanced locoregional BRAF V600E mutant melanoma patients in increasing resectability, yielding pathological responses, and achieving prolonged survival.